Strategy of Leading Madrasah Management Based on Integrated Quality Management - Arif Wahyudi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2019)
Education is the process of developing one's abilities, attitudes and other behaviors in the communities in which they live. According to Webster’s new world dictionary, education is a process of training and developing knowledge, skills, thoughts, characters, and so on. Maybe, so that there is no dichotomy of public schools with madrassas, one of which is so that madrassas always develop according to their times. Discussing about madrasas is interesting in the contemporary era. Bearing in mind, madrasas are part of the national education system that is closer and familiar to the people than other formal education systems. In the analysis of education experts, madrasas are also more strategic in achieving PUS-EFA (Education for All-Education for All), because madrasas are cheaper in terms of financing and easier to reach by the common people (grass root). This makes the madrasa increasingly find its significance in today's global competition, so madrasas can be said to be formal Islamic education institutions that greatly contribute to eradicating people's illiteracy (Indonesia).